2018
DOI: 10.1590/1807-1929/agriambi.v22n6p436-441
|View full text |Cite
|
Sign up to set email alerts
|

Isotherms and isostatic heat of foam-mat dried yellow mombin pulp

Abstract: A B S T R A C TYellow mombin has high nutritional value but is very perishable. Foam mat drying is a method that has been widely used to preserve liquid and semi-solid powdered foods. In this context, the aim of this study was to determine desorption isotherms and isosteric heat of yellow mombin (Spondias mombin L.) foam for different conditions of temperature and water activity. Powdered yellow mombin pulp was obtained by drying in forced-air oven regulated to 60 ° C. The indirect static method was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The results show that the increase in water activity represents an increase in the moisture content of grain sorghum (Sorghum bicolor (L.) Moench) flour, which is commonly found for sorption isotherms of several plant products reported in the literature, such as yellow mombin pulp (Cavalcante et al, 2018).…”
Section: Sorghum Flourmentioning
confidence: 61%
“…The results show that the increase in water activity represents an increase in the moisture content of grain sorghum (Sorghum bicolor (L.) Moench) flour, which is commonly found for sorption isotherms of several plant products reported in the literature, such as yellow mombin pulp (Cavalcante et al, 2018).…”
Section: Sorghum Flourmentioning
confidence: 61%
“…The desorption isotherm curves estimated by the model (Figure 1) showed that, for the same range of moisture content, water activity values increase as the temperature increases. It is a response found in the isotherms of various plant products in the literature, such as yellow mombin (Spondias mombin L.) pulp in foam (Cavalcante et al, 2018), sunflower seeds (Helianthus annuus L.) (Campos et al, 2019), and brazilnuts (Bertholletia excelsa H. B. K.) (Botelho et al, 2019).…”
Section: Modelmentioning
confidence: 98%
“…Comparing the values, the Chung-Pfost model obtained the lowest value (0.0029), considering that lower values for this parameter indicate less deviation of the estimated data from the experimental conditions (Eq. 9), one can compare the Chisquare values of the model fits that presented the calculated χ 2 within the confidence interval, as performed by Oliveira et al (2018).…”
Section: Isosteric Heat Of Desorptionmentioning
confidence: 99%